Dni morza : 17.VI.51-24.VI.51. - Święto Morza (1951). (Gdynia : [wydawca nieznany], 1951)
Afisz z programe obchodów w Gdańsku, Sopocie i Gdyni.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne